Utility of a personalised Bronchiectasis Action Management Plan (BAMP) for children with bronchiectasis: protocol for a multicentre, double-blind parallel, superiority randomised controlled trial. Issue 12 (22nd December 2021) - Marchant, Julie M; Chang, Anne B; Schutz, Kobi L; Versteegh, Lesley; Cook, Anne; Roberts, Jack; Morris, Peter S; Yerkovich, Stephanie T; McCallum, Gabrielle B
Abstract : Introduction: Bronchiectasis is no longer considered rare or irreversible in children, yet it remains relatively under-researched and neglected in respiratory health globally. Bronchiectasis (including chronic suppurative lung disease) causes substantial morbidity for patients and significant impact on caregivers, especially during acute respiratory exacerbations. In other chronic respiratory diseases (eg, asthma), empowering consumers with an individualised plan for management of acute exacerbations improves clinical outcomes. However, in the absence of any such data specific to bronchiectasis, action management plans are rarely currently used in children or adults with bronchiectasis. We hypothesise that providing an individualised bronchiectasis action management plan (BAMP) to children with bronchiectasis reduces non-scheduled doctor consultations, compared with not having a BAMP. Methods and analysis: This multicentre, parallel, double-blind, randomised trial involving three urban Australian hospitals commenced in June 2018 and will include 198 children, aged <19 years with bronchiectasis who had 2 or more exacerbations in the previous 18 months. Children will be randomised to having an individualised BAMP or standard care (a decoy clinic letter). Primary caregivers will then be followed up monthly for 12 months. The primary outcome is the rate of acute non-scheduled doctor visits for respiratory exacerbations by 12 months. The main secondary outcomes are cough-specific quality of life scores at 6 and 12 months, overall exacerbation rate over 12 months, and proportion of children who received timely influenza vaccination by 30 May annually. Ethics and dissemination: The Human Research Ethics Committees of the Northern Territory Department of Health and Menzies School of Heath Research and Queensland Children's Hospital approved the study. The results of the trial will be submitted for publication and the BAMP made available free online. Trial registration number: Australia and New Zealand Clinical Trials Register ACTRN12618000604202.